Relación de los factores protectores y de riesgo en las formas de presentación del asma. - Guerrón Eras, Inés Judith (2017)
The family represents the primordial unity into a big ecosystem, the balance between socio-economic factors, familiar conditions and individual health determine the family health. The prevalent sub diagnosed pathologies of the scholar phase are the asthma presentation forms, a chronic disease heterogenic and inflammatory of the respiratory track. Children with an asthma phenotype represents a vulnerable group and importance due to the repercussions that will have in their adult life. In the first childhood, there are several health determinants that may be presented from the prenatal stage, such as exposure to tobacco that can be transferred by inheritance as atopias, or may be presented in the postnatal period as exposures to aeroallergens or viruses; having underdiagnoses or inadequate treatment of this disease will influence the lung function, which determines the individual’s future life. The objective of the research was to analyze the relationship of protective or risk factors in the presentation forms of asthma. The investigation was observational, prospective, descriptive, transversal and analytical type; from an universe of 5032 children, with randomly stratified sample, 423 children of 12 to 47 months years old from the Good Living Children's Centers of the Zone 7 (CIBV) were studied; through the use of EPI INFO version 7 software; Statistical analysis was done using the SPSS v.16 software for Windows. As to the results, clinical manifestations of viral respiratory infections represent the strongest risk factor in the presentation forms of asthma, predominant in non-atopic sibilant; and the lamblia giardia as a risk factor for the transitory and atopic sibilants Keywords: asthma phenotypes, protective factors, risk factors.